2022
DOI: 10.1177/20539517221089626
|View full text |Cite
|
Sign up to set email alerts
|

(Tar)getting you: The use of online political targeted messages on Facebook

Abstract: This study examines how mainstream political actors and other organizations use political targeted messages. For this purpose, a data set from ProPublica is used. The study examines 55,918 sponsored Facebook ads that were posted by 236 political actors (i.e., political elites and other organizations) in the United States. (1) Topic classification was used to identify policy issues, (2) network analysis to identify the main policy issues from the various political actors, and (3) Sankey diagrams to visualize mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…For example, Endres (2020) found that targeting voters with congruent issues in the 2012 U.S. presidential elections was related to the mobilization of Democrats for Mitt Romney when targeted by the Republican candidate with congruent issues. A recent content analysis of TPA on Facebook before the 2018 U.S. midterm elections showed that political actors use targeted ads to tailor specific issues to voters (Kruikemeier et al, 2022). The authors further outline that while political parties mainly focus on issues they own, they also target voters with issues originally owned by other parties or with divisive issues, so-called wedge issues (see also Hillygus & Shields, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Endres (2020) found that targeting voters with congruent issues in the 2012 U.S. presidential elections was related to the mobilization of Democrats for Mitt Romney when targeted by the Republican candidate with congruent issues. A recent content analysis of TPA on Facebook before the 2018 U.S. midterm elections showed that political actors use targeted ads to tailor specific issues to voters (Kruikemeier et al, 2022). The authors further outline that while political parties mainly focus on issues they own, they also target voters with issues originally owned by other parties or with divisive issues, so-called wedge issues (see also Hillygus & Shields, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…According to the issue ownership theory, political parties are associated with owned issues, which can influence voters’ perceptions about the parties’ competencies in dealing with such issues (Walgrave et al, 2015) or can shape voters’ electoral choices (Bélanger & Meguid, 2008). A recent content analysis of sponsored Facebook ads in the United States found evidence for issue ownership patterns in political microtargeting, meaning that political actors mainly focused on owned issues (Kruikemeier et al, 2022). By focusing on specific issues and issue stances, campaigns aim for persuadable voters, engaging in issue-based targeting (Hersh & Schaffner, 2013; Hillygus & Shields, 2009).…”
Section: Effects Of Political Fit and Issue Fit On Persuasion Knowledgementioning
confidence: 99%